Prediction of improved water productivity on-farm level in the selected cotton farms of Fergana and Andijan Provinces of Uzbekistan - Jumaboev, Kahramon; Eshmuratov, Davron; Reddy, Junna Mohan; Anarbekov, Oyture; Kazbekov, Jusipbek S. (2010)
Irrigated agriculture in Central Asia can only be developed through increase of crop yields and reduction of water volumes applied per unit of agricultural production. Thus to improve agricultural production, proper agronomic measures and irrigation schedules have to be developed considering local conditions. To assess existing water productivity, 9 farms have been selected along South Fergana Canal. A Soil-Water-Air-Plant (SWAP) model has been applied for the same fields to predict potential water productivity.